Medical Pharmacology and Therapeutics by Derek G. Waller and Anthony P. Sampson - Amie Bain (University of Huddersfield Press, 2017)
A thorough and contemporaneous working knowledge of both pharmacology and therapeutics is integral to the current practice of pharmacy, and both disciplines form a significant and rudimentary part of the undergraduate curricula. It is vital that the student is able to formulate scientific rationale for the use of pharmacological agents in the treatment of disease, and that a sound underpinning knowledge of all relevant disciplines enables them to do so. Of equal importance is the ability of the teacher to present essential information about pharmacology and therapeutics as part of an integrated curricula in a way that engages the student and enhances their appreciation of the applicability of these various disciplines to clinical practice. Waller and Sampson's 'Medical Pharmacology and Therapeutics' aims to encourage a deeper understanding of the principals of drug usage by explaining the basic science underpinning clinical application of pharmacological agents. This review seeks to investigate elements that are specific to the needs of the target audience and will explore the potential of this book in achieving those aims.